Serum Human Epididymis Protein 4 as a Novel Biomarker in Identifying Patients With Interstitial Lung Disease in Rheumatoid Arthritis - Liang, Liu; Chen, Jiali; Di, Chun; Zhan, Minghua; Bao, Huizhang; Xia, Changsheng; Fan, Chunhong; Liu, Yudong (Frontiers in Medicine, 2021)
Objective. Human epididymis protein 4 (HE4) have been implicated in the pulmonary involvements. We aimed to investigate the clinical utility of HE4 in clinical stratification in patients with rheumatoid arthritis (RA). Methods. This study included a discovery cohort comprising 70 RA patients and 64 healthy controls (HCs), and a validation cohort comprising 98 RA patients and 81 HCs. HE4 were determined by electrochemical luminescence analyzer. Results. The levels of HE4 were significantly elevated in patients with RA compared to HCs. The positive rates of HE4 in patients with RA and HCs were 50.0% and 0, respectively, in the discovery cohort and 53.1% and 1.2%, respectively, in the validation cohort. When RA patients were subgrouped according to HE4 status, HE4-positive group displayed higher prevalence of interstitial lung disease (ILD) compared to HE4-negative group (28.6% vs 11.4% in discovery cohort and 57.7% vs 8.7% in the validation cohort). A positive correlation between the levels of HE4 with the degree of lung impairment was identified. Receiver operating curve (ROC) analysis revealed an optimal cut-off value of 104.3 pmol/L in HE4 for distinguishing RA-ILD from RA-non ILD with the areas under the curve (AUC) of 0.790. Multivariate logistic regression analysis illustrated that high levels of HE4 independently identified patients with RA-ILD (OR, 9.663, p<0.001). Conclusion. Our findings showed a novel role of HE4 in RA risk stratification, suggest that introducing HE4 to the current RA test panel may provide additional diagnostic value, particularly in identifying patients at risk of RA-ILD.